Efficacy of mixture of emamectin benzoate with some insecticides on the mortality and esterase activity of fourth instar larvae of Tuta absoluta (Lepidotera: Gelechiidae) - Mohsen Taleh; Hooshang Rafiee Dastjerdi; Bahram Naseri; Aziz Sheikhi Garjan; Khalil Talebi Jahromi (Journal of Crop Protection, 2020)
The tomato leafminer, Tuta absoluta Meyrick (Lepidoptera: Gelechiidae) is one of the most damaging tomato pests in the world and in Iran. The toxicity of acetamiprid, eforia (thiamethoxam + lambda-cyhalothrin) and hexaflumuron alone and in mixture with emamectin benzoate was studied against 4th-instars of Tuta absoluta (Meyrick) at 25 ± 2 °C, 65 ± 5% RH and 16:8 (L:D) h. Moreover, the mixtures of examined insecticides with emamectin benzoate at LC15:LC15 ratio were assessed on the general esterase enzyme activity and total protein content of 4th-instars. The highest toxicity was found for emamectin benzoate after 72 h (LC50 = 0.48 mg a.i./l), followed by acetamiprid (LC50 = 46.94 mg a.i./l), eforia (LC50 = 156.24 mg a.i/l) and hexaflumuron (LC50 = 670.32 mg a.i/l). Mixing emamectin benzoate with acetamiprid at the ratio of LC50:LC50 and LC25:LC25 resulted in synergistic impacts while mix of two other ratios of the same pesticides represented additive influences. The mixture of emamectin benzoate with either hexaflumuron or eforia at all ratios created antagonistic and additive effects, respectively. Mixing emamectin benzoate with either acetamiprid or eforia increased larval esterase activity, however, there was no significant difference between emamectin benzoate in mixture with hexaflumuron and using it alone. Mixing emamectin benzoate with the examined insecticides considerably decreased the larval total protein content. Based on the findings of this work, the mixtures of eforia and acetamiprid with emamectin benzoate represented greater negative effects against 4th-instars compared to emamectin benzoate alone and the control.